(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper investigates the impact of artificial intelligence (AI) and automation on the engineering workforce. The research will explore how these technologies are changing the roles and responsibilities of engineers. The paper will then discuss how engineering leaders can adapt their leadership styles and approaches to effectively manage and motivate teams working alongside AI and automation.